2020
DOI: 10.3389/fonc.2020.599250
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Confocal Laser Endomicroscopy Ex Vivo Examination of Tissue Microstructure During Fluorescence-Guided Brain Tumor Surgery

Abstract: BackgroundNoninvasive intraoperative optical biopsy that provides real-time imaging of histoarchitectural (cell resolution) features of brain tumors, especially at the margin of invasive tumors, would be of great value. To assess clinical-grade confocal laser endomicroscopy (CLE) and to prepare for its use intraoperatively in vivo, we performed an assessment of CLE ex vivo imaging in brain lesions.MethodsTissue samples from patients who underwent intracranial surgeries with fluorescein sodium (FNa)–based wide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 34 publications
4
60
0
Order By: Relevance
“…Alternatively, fluorescein could be combined with Raman spectroscopy, which has been shown to accurately delineate tumor versus normal brain at the margins of resection, with superior performance compared to 5-ALA (55). Confocal laser endomicroscopy has also been combined with fluorescein and recently investigated as a means of increasing extent of resection by providing real-time intraoperative verification of pathologic tumor tissue (56)(57)(58). Several studies have also mentioned the potential benefit of quantitatively measuring fluorescence intensity and integrating this technology with the operative microscope, which could increase both the safety and the sensitivity of fluorescein as an adjunct for glioma resection (9,17,29).…”
Section: Future Directionsmentioning
confidence: 99%
“…Alternatively, fluorescein could be combined with Raman spectroscopy, which has been shown to accurately delineate tumor versus normal brain at the margins of resection, with superior performance compared to 5-ALA (55). Confocal laser endomicroscopy has also been combined with fluorescein and recently investigated as a means of increasing extent of resection by providing real-time intraoperative verification of pathologic tumor tissue (56)(57)(58). Several studies have also mentioned the potential benefit of quantitatively measuring fluorescence intensity and integrating this technology with the operative microscope, which could increase both the safety and the sensitivity of fluorescein as an adjunct for glioma resection (9,17,29).…”
Section: Future Directionsmentioning
confidence: 99%
“…In this work the authors provided 3D images of different kind of brain tumors, suggesting that this technology may afford an increased spatial understanding of tumor cellular architecture and visualization of related structures compared with two-dimensional images. In 2020, the same group tested for the first time the feasibility of positioning the Convivo probe in a trans-sphenoidal corridor in cadaver heads and obtained 19 biopsies from nine patients who underwent pituitary adenoma surgery for ex vivo imaging at various times after fluorescein injection [ 41 ]. A blinded board-certified neuropathologist analyzed the images, resulting in a 8/13 pituitary adenomas correctly identified through CLE analysis using frozen sections as the standard.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent works by Belykh and colleagues, the dye was studied for ex-vivo pituitary tumors analysis, identifying the correct timing for SF administration in respect to biopsy procedure [ 45 ]. In 2020 the authors reported for the first time the increasing diagnostic power that a second intravenous injection of such dye may confer in the analysis of intracranial lesions [ 41 ]. Thanks to its proven effect in increasing EOR and ability to enhance CLE images, highlighting tumor cells in fluorescent areas, to date this dye appears to be one of the best contrast enhancers that can be coupled to confocal imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, e x vivo imaging after topical staining is significantly less affected by the timing of fluorescein administration. Insufficient contrast can be avoided by readministration of fluorescein and thus increase image quality ( 32 ). Future analysis will include an assessment of tumor microvasculature in addition to tumor cell morphology and architecture.…”
Section: Discussionmentioning
confidence: 99%